Evaluating the Performance of a Small‐Scale Culture System for Delta Smelt. (24th May 2022) - Tsai, Yi‐Jiun Jean; Ellison, Luke; Stevenson, Troy; Mulvaney, William J.; Carson, Evan W.; Hung, Tien‐Chieh
Abstract: Since 2008, a refuge population of Delta Smelt Hypomesus transpacificus has been cultured in a conservation hatchery to help protect the imperiled species from extinction. Culture techniques for this population have thus far focused on maximizing genetic diversity in conjunction with large‐scale operations (40 larval tanks, 5, 954‐L larval system, 224, 000 larvae capacity), which includes rearing multiple family groups within the same tanks. However, Delta Smelt production and associated research projects would benefit from also being able to rear fish on a smaller scale, such as in individual family groups. Recently, a new culture system and modified culture practices were developed for rearing small groups of larval Delta Smelt. We (1) determined the performance of the small‐scale "experimental" rearing system from embryo to 80 d posthatch (dph) and (2) tested whether the performance of the experimental system met the standard set by the large‐scale "refuge" rearing system at critical culturing life stages in terms of embryo hatching rate (10 d postfertilization) and larval survival, length, and weight (40 and 80 dph). From 1, 000 embryos, the experimental system produced a mean ± SE of 376 ± 44 late‐stage larvae. The hatching rate of embryos did not differ between systems. Early‐stage larvae (0–40 dph) reared in the experimental system did not differ in survival rate but were longer and heavier than those reared in the refuge system. In contrast, late‐stage larvae (41–80 dph) reared in the experimental system had poorer survival and were shorter and lighter than refuge‐reared larvae. Thus, the experimental system met the refuge‐system benchmark for embryo hatching and exceeded the benchmark in early‐larval production, but it could be improved for late‐larval rearing. Nevertheless, this small‐scale rearing system will provide much‐needed flexibility to enhance Delta Smelt culture practices and facilitate future research.